Robots [videorecording (DVD)] - Wedge, Chris, 1958-; Saldanha, Carlos, 1965-; McGregor, Ewan, 1971-; Berry, Halle; Kinnear, Greg, 1963-; Brooks, Mel, 1926-; Bynes, Amanda, 1986-; Carey, Drew; Broadbent, Jim; Tucci, Stanley; Williams, Robin, 1951-2014 (20th Century Fox Home Entertainment, 2005)
With the help of his misfit mechanical friends, a small town robot named Rodney embarks on the adventure of a lifetime as he heads for the big city to pursue his dreams and ultimately proves that anyone can shine no matter what they're made of.